LEARNING THE INTEGRATION OF ISLAMIC SCIENCES IN THE 5.0 ERA - siti aliyah; Khuriyah Khuriyah; Fitri Wulandari (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This study looks at the conception of integration of knowledge, internal integration in Islamic Religious Education (PAI) subjects and discussion of the new era of Society 5.0 as a phenomenon of the fusion of the virtual dimension of technology with the real dimension which is marked by the connection of various places through the accumulation of even distribution of information and knowledge. This has implications for the dynamics of sociological change in Indonesian society which has a variety of races, ethnicities, religions and cultures, as well as providing new challenges for the world of Islamic education. PAI learning takes place formally in real and virtual classes. This research is a qualitative research using the study literature method. This method collects information or data through books, journals or articles that are relevant to the issue being studied. The mushrooming of material content of Islamic values ??in the world of social media makes it possible for people to obtain information on Islamic knowledge without having to come to the science assembly directly. This will reap benefits and harm if it is not accompanied by a complete understanding so that scientific knowledge is still connected to the initial source, namely the learning of Islamic religious values ??brought by Rasulullah SAW.